After Balanced Scoredcards Implementation: What Changes Does It Bring? (a Case of Ministry of Foreign Affairs Indonesia) - Sirait, Bernard (JPAS (Journal of Public Administration Studies), 2018)
This paper aims to study the result of BSC implementation in Public Sector especially MoFA of the Republic of Indonesia and the impacts of BSC to MoFAâ€™s performance indicators. The study used content analysis combined with the descriptive method in processing the data. Secondary data used were MoFAâ€™s performance documents â€œLaporan Kinerja Tahunanâ€ (LKJ) within 2014-2016. The result implied that BSC implementation has improved the number of MoFAâ€™s Key Performance Indicator (KPI) significantly. It also affect human resources management situation. Moreover, the implementation of BSC has improved performance achievement of the MoFAâ€™s KPI. However, the limitation of this paper is that the data used in this study is only secondary data about MoFAâ€™s performance. The LKJ was submitted in order to fulfil the accountability obligation, and the achievement were mostly claimed by MoFA itself. This study give evidence of BSC implementation in public sector in Indonesia, a developing country. It suggests that public institution need to consider BSC implementation seriously, due to public performance improvement.